PADRÃO ALIMENTAR E DISLIPIDEMIA EM ADOLESCENTES DE ESCOLAS PÚBLICAS DE UMA CAPITAL DO NORDESTE BRASILEIRO - PIRES, Bruna Renata Fernandes (2017)
Studies developed in Brazil have shown that the lipid profile of adolescents is undergoing changes. Probably due to changes that the dietary patterns of this population have been suffering over the years. However, there are few studies on the relationship between dietary patterns and dyslipidemia in adolescents, especially in the Northeast of Brazil. Objective: To analyze the association between dietary patterns and dyslipidemia in adolescents. Material and methods: Cross-sectional study with 363 adolescents of both sexes, ages 17 to 18, from public schools of São Luís, Maranhão. Food consumption was evaluated by means of a Food Frequency Questionnaire (FFQ) and the dietary patterns were identified by Principal Component Analysis (PCA). Adolescents who had an alteration in at least one of the following conditions were considered dyslipidemia carriers: total cholesterol (TC), low density lipoprotein (LDL-c), high density lipoprotein (HDL-c), triglycerides (TG), Index of Castelli I and II and No HDL-c. For selection of the variables that were controlled in the analysis of the effect of dietary patterns on the dyslipidemias, we used the Directed Acyclic Graphs (DAG) and the final sample was weighted to the inverse of the probability of selection for these variables through doubly robust method. Results: Three dietary patterns were identified in this study: “Western” (stuffed cookie, cake, soft drinks, processed juices, coffee/ tea with sugar, red meat/ viscera, fast food, sugar/ sweets), “Healthy” (vegetables, fruits, natural juices, nonfat milk/ derivatives, coffee/ tea without sugar, legumes, light butter/ margarine and salad dressings), and “Traditional” (breads/ cookies without filling, butter/ margarine, whole milk/ milk products, beans, rice, cereals and eggs). Most of the adolescents showed dyslipidemia (59.23%), and the inadequacy of HDL-c levels was the primary dyslipidemia found (44.9%). There was no significant difference in the occurrence of dyslipidemia among the three identified dietary patterns (p>0.05). Conclusion: The study population had a high prevalence of dyslipidemia. However, the adolescents’ dietary pattern did not explain dyslipidemia.